Implementasi Metode Simple Additive Weighting (SAW) Dalam Penilaian Kinerja Karyawan Pada LPK Pelita Massa Berbasis Web - Rizal Rosidin; Yudi Ramdhani (CV. Ulil Albab Corp, 2022)
Although employee performance assessments at LPK Pelita Massa have not yet been implemented, the company itself has plans to implement employee performance appraisals. Employee performance appraisals can motivate employees and increase employee loyalty to the company. However, the LPK Pelita Massa still finds it difficult to decide on the best employees according to the criteria. A technique to overcome a problem in terms of systematic and unsystematic is also called a decision support system (DSS). The Simple Additive Weighting (SAW) method will be implemented into a decision support system in the hope of being a solution to the problems experienced by LPK Pelita Massa in determining the best employees. The results of interviews and observations at LPK Pelita Massa became the primary data for this study in determining the criteria and alternatives, and five (5) criteria were obtained, namely responsibility, work knowledge, cooperation, work quality, and attitude, after knowing the criteria, then doing calculations, and ranking alternatives. A Web-based decision support system is the result of this research